Giving Sustainability a Chance: A Participatory Framework for Choosing between Alternative Futures. (April 2015) - Sajeva, Maurizio; Sahota, Parminder Singh; Lemon, Mark
Abstract : This article analyses the concepts of sustainability and governance from a holistic and systemic perspective. It avoids predictive and positivist evaluation approaches and commences with a rejection of natural, human, and social capital being measurable in monetary terms, due to the high level of uncertainty relating to what constitutes a sustainable future. A qualitative-based methodology, grounded in the five capitals model of Forum for the Future, is explored for the evaluation of sustainability. On the basis of some main critical aspects, which are common to various socio-technological systems, this approach identifies criteria for a generalised governance assessment methodology for evaluating the possibility of systems for more sustainable futures. Underpinning these criteria is a multidisciplinary approach, a 'Governance Assessment Matrix Exercise' (GAME), which provides a toolkit for setting general criteria for sustainability for each of the dimensions of the five capitals model and choosing between alternative futures through a participatory process of stakeholder engagement. The central theme of the article is that the choice between alternative futures should be participatory in nature and the success of this process can be aided by an acceptance of a commonly derived set of sustainability criteria supported by a governance structure. The approach can be described as a process of social learning through which participants can understand and explore the implications of different actions and policies and select potentially more sustainable choices.